AKIBAT HUKUM PENDIRIAN PERSEROAN TERBATAS PERORANGAN TANPA AKTA NOTARIS MERUJUK PADA UNDANG-UNDANG CIPTA KERJA DITINJAU DARI KEPASTIAN HUKUM - Putri Pertiwi S, Santika; Natasya Sirait, Ningrum; Siregar, Mahmul (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
One of the updates presented through UUCK also has an impact on the provisions in UUPT, namely the recognition of a legal entity of an Individual PT that meets the criteria of micro and small businesses that do not require a Notary deed in the process of establishing it. The simplification of these provisions has brought in practice various problems. The absence of a notary position in the establishment of an Individual PT can result in a legal vacuum when determining the clarity of the deed and the authenticity of the deed that is opened online in recording the establishment of an Individual PT. This research is a normative juridical legal research with a descriptive research nature. The research approach uses a regulatory approach (statutory approach) and a contextual approach (conceptual approach). The data used is secondary data consisting of primary, secondary and tertiary legal materials. Data collection techniques and tools use literature studies and field studies through interviews with Notaries, the Regional Office of Law and Human Rights and banks. Based on the research results, it was found that the non-obligation to establish an Individual PT using a Notarial Deed aims to make it easier for MSMEs to develop their businesses by forming a legal entity in the form of a Limited Liability Company at a low cost and quickly as long as it meets the MSME criteria. However, on the other hand, the establishment of an Individual PT does not provide legal certainty because a notarial deed is seen as binding and perfect evidence. A notary is able to guarantee the capabilities of the founder through the company's deed of establishment and is able to provide legal certainty.